Thermoplastic elastomer composition and molded article

JP2025036117APending Publication Date: 2025-03-14TORAY INDUSTRIES INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024105875
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-29
Filing Date
2024-07-01
Publication Date
2025-03-14

Smart Images

  • Figure 2025036117000001
    Figure 2025036117000001
Patent Text Reader

Abstract

To provide a thermoplastic elastomer composition which is excellent in vibration damping property, spinnability, high temperature rigidity and blocking resistance.SOLUTION: A thermoplastic elastomer composition is prepared by compounding a polyamide resin (A) having a melting point by differential scanning calorimetry (DSC) of 200°C or higher and an amino terminal group amount of 4.7×10-5 to 8.0×10-5 mol / g, and a copolymer (B) which contains a polymer block mainly containing an aromatic vinyl-based compound having a reactive functional group and a polymer block mainly containing a conjugated diene-based compound and / or its hydrogenated product and has a glass transition temperature of -20°C or higher and 50°C or lower, wherein a composition ratio (weight ratio) (A):(B) of the polyamide resin (A) to the copolymer (B) is 50:50 to 80:20.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is directed to a composition comprising a polyamide resin (A) and an aromatic vinyl compound having a reactive functional group. The present invention relates to a thermoplastic elastomer composition comprising a copolymer (B) containing a polymer block having a structure represented by the formula (1) and a polymer block mainly made of a conjugated diene compound and / or a hydrogenated product thereof, and to molded articles, fibers, sheets, and foam-molded articles using the same. [Background technology]

[0002] Conventionally, flexible polymer materials have been crosslinked with rubbers such as natural rubber or synthetic rubber. In general, rubbers that are crosslinked under high temperature and pressure after mixing with additives and reinforcing agents are used. However, such rubbers require a process of crosslinking and molding under high temperature and pressure for a long period of time, and have problems such as poor processability. In addition, since crosslinked rubber does not exhibit thermoplasticity, it is generally impossible to recycle it like thermoplastic resins. For this reason, various thermoplastic elastomers that can be easily manufactured into molded products using general melt molding techniques such as injection molding, hot press molding, and extrusion molding in the same way as ordinary thermoplastic resins have been developed in recent years.

[0003] Patent Document 1 discloses a thermoplastic resin composition having a good balance between rigidity and impact resistance, the thermoplastic resin composition comprising, as main components, a modified conjugated diene polymer having at least one group selected from the group consisting of an alkoxysilyl group, an amino group, an acid anhydride group, and a carboxyl group, and a polar resin. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-291117 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the example specifically disclosed in Patent Document 1 is a resin composition consisting of a diene copolymer having a reactive functional group and polyamide 6, but the loss tangent of the resin composition at 23°C is low and excellent vibration damping properties could not be obtained.

[0006] An object of the present invention is to provide a thermoplastic elastomer composition which can be easily molded and has improved high-temperature rigidity, vibration damping properties, and spinnability. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention has the following configuration. (1) A melting point of 200°C or higher as measured by differential scanning calorimetry (DSC) and an amino end group content of 4.7 x 10 -5 ~8.0×10 -5 The thermoplastic elastomer composition is a compound comprising: (A) mol / g polyamide resin; and (B) copolymer having a glass transition temperature of -20°C or more and 50°C or less, the copolymer including a polymer block mainly made of an aromatic vinyl compound having a reactive functional group and a polymer block mainly made of a conjugated diene compound and / or a hydrogenated product thereof, the composition ratio (weight ratio) of the polyamide resin (A) to the copolymer (B) being (A):(B) = 50:50 to 80:20. (2) The thermoplastic elastomer composition according to (1), wherein the polyamide resin (A) has a relative viscosity of 1.5 to 3.0 in a 98% concentrated sulfuric acid solution having a resin concentration of 0.01 g / ml at 25° C. (3) The thermoplastic elastomer composition according to (1) or (2), wherein the polymer block mainly composed of a conjugated diene compound and / or its hydrogenated product is a polymer block derived from at least one member selected from the group consisting of isoprene, butadiene, ethylene-butylene, and ethylene-propylene. (4) The thermoplastic elastomer composition according to any one of (1) to (3), characterized in that the thermoplastic elastomer composition has a loss tangent of 0.05 or more at a frequency of 100 Hz and a temperature of 23°C. (5) A molded article made of the thermoplastic elastomer composition according to any one of (1) to (4). (6) A fiber made of the thermoplastic elastomer composition according to any one of (1) to (4). (7) A sheet made of the thermoplastic elastomer composition according to any one of (1) to (4). (8) A foam-molded article made of the thermoplastic elastomer composition according to any one of (1) to (4). Effect of the Invention

[0008] The thermoplastic elastomer composition of the present invention can be easily molded using general-purpose melt molding techniques, and has excellent vibration damping properties, spinnability, high-temperature rigidity and blocking resistance, and can be used in, for example, automotive applications, electrical and electronic applications, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will now be described in further detail.

[0010] The present invention relates to a compound having a melting point of 200° C. or higher as measured by differential scanning calorimetry (DSC) and an amino terminal group content of 4.7×10 -5 ~8.0×10 -5 The thermoplastic elastomer composition is a compound comprising a polyamide resin (A) of 1.0 mol / g (hereinafter sometimes abbreviated as polyamide resin (A)) and a copolymer (B) (hereinafter sometimes abbreviated as copolymer (B)) having a glass transition temperature of -20°C or more and 50°C or less, the copolymer (B) comprising a polymer block mainly made of an aromatic vinyl compound having a reactive functional group and a polymer block mainly made of a conjugated diene compound and / or a hydrogenated product thereof.

[0011] This product has excellent properties such as excellent high-temperature rigidity and moldability. By blending polyamide resin (A), which has a specific amount of amino terminal groups, with copolymer (B), which has reactive functional groups and a specific glass transition temperature, in a specific ratio, polyamide resin (A) reacts appropriately with copolymer (B), resulting in good compatibility between polyamide resin (A) and copolymer (B). This product can be endowed with properties that combine the moldability, such as high-temperature rigidity and blocking resistance and spinnability, of polyamide, with the flexibility and vibration damping properties of copolymer.

[0012] The polyamide resin (A) used in the present invention has a melting point of 200° C. or higher as measured by DSC and an amino terminal group content of 4.7×10 -5 ~8.0×10 -5 mol / g of polyamide resin.

[0013] The melting point of the polyamide resin (A) in the present invention by DSC can be determined by the following method. First, a differential scanning calorimeter (DSC-7 manufactured by PerkinElmer) is used, and two-point calibration (indium, lead) and baseline correction are performed. 8 to 10 mg of a polyamide resin sample is weighed out, and the sample is heated at a heating rate of 20°C / min, and the melting endothermic peak observed during the heating process is taken as the melting point.

[0014] If the melting point of the polyamide resin (A) is lower than 200° C., the high-temperature rigidity of the thermoplastic elastomer composition of the present invention decreases. The melting point of the polyamide resin (A) is preferably 205° C. or higher, and more preferably 210° C. or higher.

[0015] On the other hand, the upper limit of the melting point of the polyamide resin (A) is not particularly limited, but is preferably 350°C or less, since this tends to suppress decomposition of the copolymer (B) and prevent a decrease in mechanical properties, more preferably 320°C or less, and even more preferably 300°C or less.

[0016] Examples of means for adjusting the melting point of the polyamide resin (A) within the above range include a method of selecting one having a desired melting point from polyamide resins having different melting points, and a method of adjusting the polymerization degree or copolymerization ratio of the polyamide resin.

[0017] The amount of amino terminal groups in the polyamide resin (A) in the present invention can be determined by the following method: dissolving the polyamide resin in a phenol / ethanol mixed solvent (volume ratio of 83.5:16.5) and titrating with a 0.02N aqueous hydrochloric acid solution.

[0018] The amount of amino terminal groups in polyamide resin (A) is 4.7×10 -5 If the amount is less than 8.0×10 mol / g, the reactivity with the copolymer (B) decreases, and the dispersion structure becomes coarse, resulting in poor spinnability. -5 If it is more than mol / g, the reaction with the copolymer (B) proceeds too far, causing gelation and decreasing spinnability.

[0019] The polyamide resin (A) is not particularly limited as long as it is a polyamide resin whose melting point and amino terminal group amount satisfy the above-mentioned conditions, but it can generally be obtained using amino acids, lactams or diamines and dicarboxylic acids as main raw materials. Representative examples of the raw material include amino acids such as 6-aminocaproic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid, and para-aminomethylbenzoic acid; lactams such as ε-caprolactam and ω-laurolactam; aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, 2-methylpentamethylenediamine, undecamethylenediamine, dodecamethylenediamine, 2,2,4- / 2,4,4-trimethylhexamethylenediamine, and 5-methylnonamethylenediamine; aromatic diamines such as metaxylylenediamine and paraxylylenediamine; 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane, bis Alicyclic diamines such as (4-aminocyclohexyl)methane, bis(3-methyl-4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminopropyl)piperazine, and aminoethylpiperazine; aliphatic dicarboxylic acids such as adipic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2-chloroterephthalic acid, 2-methylterephthalic acid, 5-methylisophthalic acid, 5-sodiumsulfoisophthalic acid, hexahydroterephthalic acid, and hexahydroisophthalic acid; and alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, and 1,3-cyclopentanedicarboxylic acid. In the present invention, polyamide homopolymers or copolymers derived from these raw materials can be used. Two or more of such polyamide resins may be used.

[0020] Specific examples of the polyamide resin (A) preferably used in the present invention include polycaproamide (polyamide 6), polyhexamethylene adipamide (polyamide 66), polytetramethylene adipamide (polyamide 46), polyhexamethylene sebacamide (polyamide 610), polyhexamethylene dodecamide (polyamide 612), polyhexamethylene terephthalamide / polycaproamide copolymer (polyamide 6T / 6), polyhexamethylene adipamide / polyhexamethylene terephthalamide copolymer (polyamide 66 / 6T), polyhexamethylene adipamide / polyhexamethylene Examples of the polyamide include polyamide 66 / 6I, polyhexamethylene adipamide / polyhexamethylene terephthalamide / polyhexamethylene isophthalamide copolymer (polyamide 66 / 6T / 6I), polyhexamethylene terephthalamide / polyhexamethylene isophthalamide copolymer (polyamide 6T / 6I), polyhexamethylene terephthalamide / poly(2-methylpentamethylene) terephthalamide copolymer (polyamide 6T / M5T), polyxylylene adipamide (polyamide XD6), and mixtures or copolymers thereof. Particularly preferred are polyamide 6, polyamide 610, and polyamide 66, and more preferred is polyamide 6.

[0021] Although there is no particular restriction on the degree of polymerization of the polyamide resin (A), the relative viscosity of a 98% concentrated sulfuric acid solution having a resin concentration of 0.01 g / ml at 25° C. is preferably 1.5 to 3.0. If the relative viscosity is 1.5 or more, the melt viscosity of the polyamide resin composition during molding becomes appropriately high, which can suppress air entrapment during molding and further improve moldability. The relative viscosity is more preferably 1.8 or more. On the other hand, if the relative viscosity is 3.0 or less, the melt viscosity of the polyamide resin composition during spinning becomes appropriately low, which can further improve spinnability.

[0022] The copolymer (B) used in the present invention is a copolymer having a glass transition temperature of -20°C or more and 50°C or less, which contains a polymer block mainly composed of an aromatic vinyl compound having a reactive functional group and a polymer block mainly composed of a conjugated diene compound and / or a hydrogenated product thereof.

[0023] The reactive functional group in the copolymer (B) is not particularly limited, and examples thereof include at least one selected from an amino group, a carboxyl group, a carboxyl metal salt, a hydroxyl group, an acid anhydride group, an epoxy group, an isocyanate group, a mercapto group, an oxazoline group, a sulfonic acid group, etc. Among these, an amino group, a carboxyl group, a carboxyl metal salt, an epoxy group, an acid anhydride group, and an oxazoline group are preferably used because they have high reactivity and cause few side reactions such as decomposition and crosslinking.

[0024] Examples of the acid anhydride constituting the acid anhydride group include maleic anhydride, itaconic anhydride, endic anhydride, citraconic anhydride, and 1-butene-3,4-dicarboxylic anhydride. Two or more of these may be used in combination. Of these, maleic anhydride and itaconic anhydride are preferably used.

[0025] The polymer block mainly composed of an aromatic vinyl compound is a polymer block composed of 60% by weight or more, preferably 70% by weight or more, and more preferably 80% by weight or more of units derived from an aromatic vinyl compound.

[0026] Examples of aromatic vinyl compounds include styrene, α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,6-dimethylstyrene, 2,4-dimethylstyrene, α-methyl-o-methylstyrene, α-methyl-m-methylstyrene, α-methyl-p-methylstyrene, β-methyl-o-methylstyrene, β-methyl-m-methylstyrene, β-methyl-p-methylstyrene, 2,4,6-trimethylstyrene, α-methyl-2,6-dimethylstyrene, α-methyl-2,4-dimethylstyrene, β-methyl-2,6-dimethylstyrene, β-methyl-2,4-dimethylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, 2,6-dichlorostyrene, 2,4-dichlorostyrene, and α-chloro-o-chlorostyrene. , α-chloro-m-chlorostyrene, α-chloro-p-chlorostyrene, β-chloro-o-chlorostyrene, β-chloro-m-chlorostyrene, β-chloro-p-chlorostyrene, 2,4,6-trichlorostyrene, α-chloro-2,6-dichlorostyrene, α-chloro-2,4-dichlorostyrene, β-chloro-2,6-dichlorostyrene, β-chloro-2,4-dichlorostyrene, ot-butylstyrene, mt-butylstyrene, pt-butylstyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-chloromethylstyrene, m-chloromethylstyrene, p-chloromethylstyrene, o-bromomethylstyrene, m-bromomethylstyrene, p-bromomethylstyrene, styrene derivatives substituted with silyl groups, indene, vinylnaphthalene, etc. Among these, styrene, α-methylstyrene, and mixtures thereof are preferred from the viewpoints of industrial availability and glass transition temperature.

[0027] The polymer block mainly composed of a conjugated diene compound is a polymer block composed of 60% by weight or more, preferably 70% by weight or more, and more preferably 80% by weight or more of units derived from a conjugated diene compound.

[0028] Examples of the conjugated diene compound include butadiene, isoprene, 1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 1,3-hexadiene, and hydrogenated products thereof, etc. One or more of these are selected and used.

[0029] Preferred conjugated diene compounds are isoprene, butadiene, ethylene-butene which is a hydrogenated butadiene, and ethylene-propylene which is a hydrogenated isoprene.

[0030] There is no particular restriction on the ratio of the polymer block mainly made of an aromatic vinyl compound to the polymer block mainly made of a conjugated diene compound, but from the viewpoint of loss tangent, the content of the polymer block mainly made of an aromatic vinyl compound in the copolymer (B) is preferably 10 to 50% by weight, more preferably 10 to 40% by weight. When the content of the polymer block mainly made of an aromatic vinyl compound is 10% by weight or more, sufficient mechanical properties are exhibited, and when it is 50% by weight or less, the loss tangent can be increased.

[0031] The molecular weight of the copolymer (B) is not particularly limited, but in terms of moldability, fluidity, rubber elasticity, etc., the weight average molecular weight measured by GPC is preferably 5,000 to 400,000, and more preferably 10,000 to 200,000. If the weight average molecular weight is 5,000 or more, sufficient mechanical properties are exhibited, while if it is 400,000 or less, the molded product will have excellent processability and fluidity.

[0032] The amount of reactive functional group introduced into copolymer (B) is preferably 0.1 to 5 parts by weight, more preferably 0.1 to 4 parts by weight, and even more preferably 0.5 to 3 parts by weight, based on 100 parts by weight of copolymer (B). By making the amount of reactive functional group introduced 0.1 parts by weight or more, the reactivity with polyamide resin (A) can be increased, and the dispersion structure can be made finer, thereby improving spinnability. On the other hand, if the amount of reactive functional group is more than 5 parts by weight, the reaction between polyamide resin (A) and copolymer (B) proceeds excessively, and gelation proceeds, thereby decreasing spinnability.

[0033] The glass transition temperature of the copolymer (B) in the present invention is from −20° C. to 50° C. By having the glass transition temperature of the copolymer (B) from −20° C. to 50° C., the loss tangent at a frequency of 100 Hz and a temperature of 23° C. of the thermoplastic elastomer composition can be increased.

[0034] The glass transition temperature of the copolymer (B) is preferably from -20°C to 40°C, more preferably from -15°C to 35°C.

[0035] The glass transition temperature of the copolymer (B) can be determined by the following method. A sample kept in an absolute dry state is measured in a nitrogen atmosphere at a frequency of 10 Hz and a heating rate of 2°C / min using a viscoelasticity measuring device (Seiko Instruments, DMS6100), to determine the storage modulus and loss modulus. The loss modulus is divided by the storage modulus to determine the loss tangent. The temperature at the peak position of the loss tangent obtained at this time is taken as the glass transition temperature. Examples of methods for adjusting the glass transition temperature of the copolymer (B) include a method of randomly incorporating an aromatic vinyl component in addition to a conjugated diene compound component into a polymer block mainly composed of a conjugated diene compound, and a method of using a conjugated diene compound that exhibits a high Tg.

[0036] The blending amount of polyamide resin (A) and copolymer (B) in the present invention is such that the ratio (weight ratio) of polyamide resin (A) to copolymer (B) (A):(B) is 50:50 to 80:20. If the amount of copolymer (B) is greater than 50:50, the reaction between polyamide resin (A) and copolymer (B) proceeds excessively, and the high-temperature rigidity of the polyamide resin is not expressed. On the other hand, if the amount of copolymer (B) is less than 80:20, the loss tangent of the thermoplastic elastomer composition is low, and vibration damping properties cannot be imparted. (A):(B) is 50:50 to 80:20, and preferably 55:45 to 75:25.

[0037] The loss tangent of the thermoplastic elastomer composition of the present invention is preferably 0.05 or more at a frequency of 100 Hz and a temperature of 23° C. By making the loss tangent at a frequency of 100 Hz and a temperature of 23° C. 0.05 or more, it is possible to impart vibration damping properties to a molded article made of the thermoplastic elastomer composition.

[0038] The loss tangent at a frequency of 100 Hz and a temperature of 23° C. can be determined by the following method. The thermoplastic elastomer composition is measured using a viscoelasticity measuring device (Seiko Instruments, DMS6100) under nitrogen atmosphere, at a heating rate of 2° C. / min and a frequency of 100 Hz to determine the storage modulus and loss modulus. The loss modulus at 23° C. is divided by the storage modulus to determine the loss tangent at 23° C.

[0039] In order to achieve a loss tangent of 0.05 or more at a frequency of 100 Hz and a temperature of 23° C., the ratio (weight ratio) of polyamide resin (A) to copolymer (B) (A:B) should be 50:50 to 80:20.

[0040] The loss tangent at a frequency of 100 Hz and a temperature of 23° C. is preferably 0.05 or more, more preferably 0.07 or more, and even more preferably 0.10 or more.

[0041] There is no particular upper limit to the loss tangent at a frequency of 100 Hz and a temperature of 23° C., but from the viewpoint of maintaining the shape of the molded product, it is preferably 5.0 or less.

[0042] The thermoplastic elastomer composition of the present invention has excellent spinnability.

[0043] Spinnability can be confirmed by the following method. Thermoplastic elastomer composition pellets are vacuum dried at 80°C for 15 hours. The vacuum dried pellets are filled into a cylinder set at a test temperature of 280°C using a Toyo Seiki Co., Ltd. Capillograph 1C (cylinder diameter 9.55 mm, orifice length 10.0 mm, inner diameter 1.0 mm), and the thermoplastic elastomer composition is compressed and held for 30 minutes to melt it, and then discharged at an extrusion speed of 3 mm / min. The discharged thermoplastic elastomer composition is taken up while changing the take-up speed, and spinnability is confirmed.

[0044] For excellent spinnability, the amino end group content is 4.7 × 10 -5 ~8.0×10 -5 It is preferable to use a polyamide resin (A) having a relative viscosity of 1.5 to 3.0 mol / g and a resin concentration of 0.01 g / ml at 25°C in a 98% concentrated sulfuric acid solution, and a copolymer (B) having an introduced amount of reactive functional groups of 0.1 to 5 parts by weight, and to mix these compounds in a ratio (weight ratio) of (A):(B) of 50:50 to 80:20.

[0045] The thermoplastic elastomer composition of the present invention has excellent sheet moldability.

[0046] Sheet moldability can be confirmed by the following method. Thermoplastic elastomer composition pellets are vacuum dried at 80°C for 15 hours. The vacuum dried pellets are melted and kneaded in an extruder, the resin is extruded in a certain direction from a mold, and formed into a sheet by fixing it on a roll, and the sheet moldability is confirmed.

[0047] In order to have excellent sheet formability, the amino end group content is 4.7 × 10 -5 ~8.0×10 -5It is preferable to use mol / g polyamide resin (A) and copolymer (B) having 0.1 to 5 parts by weight of reactive functional group introduced therein, and mix them in a ratio (weight ratio) of (A):(B) of 50:50 to 80:20.

[0048] The thermoplastic elastomer composition of the present invention has excellent high-temperature stiffness.

[0049] Here, the melting point of the thermoplastic elastomer composition is used as an index of high-temperature rigidity. The higher the melting point of the thermoplastic elastomer composition, the better the high-temperature rigidity is judged to be. From the viewpoint of shape retention of the molded product, the melting point of the thermoplastic elastomer composition is preferably 200°C or higher. The melting point of the thermoplastic elastomer composition is preferably 200°C or higher, more preferably 205°C or higher, and even more preferably 210°C or higher.

[0050] On the other hand, there is no particular upper limit to the melting point of the thermoplastic elastomer composition, but from the viewpoint of productivity, it is preferably 350° C. or lower, more preferably 320° C. or lower, and even more preferably 300° C. or lower.

[0051] The melting point of the thermoplastic elastomer composition of the present invention can be determined by the following method. First, a differential scanning calorimeter (DSC-7 manufactured by PerkinElmer) is used to perform two-point calibration (indium, lead) and baseline correction. 8 to 10 mg of a sample of the thermoplastic elastomer composition is weighed out, and the sample is heated at a heating rate of 20°C / min. The melting endothermic peak observed during the heating process is taken as the melting point.

[0052] The melting point of the thermoplastic elastomer composition can be adjusted to fall within the above range, for example, by using a polyamide resin (A) having a melting point of 200° C. or higher as measured by DSC.

[0053] The thermoplastic elastomer composition of the present invention may contain, if necessary, 0 to 70 parts by weight of other components per 100 parts by weight of the total of the polyamide resin (A) and the copolymer (B) within a range that does not impair the properties of the composition. Examples of other components include fillers, copper compounds, potassium compounds, thermoplastic resins other than the component (A), rubbery polymers other than the component (B), and various additives.

[0054] For example, by blending a filler, the strength and dimensional stability of the molded product can be improved. The shape of the filler may be fibrous or non-fibrous, and a combination of a fibrous filler and a non-fibrous filler may be used. Examples of fibrous fillers include glass fiber, glass middle fiber, carbon fiber, potassium titanate whisker, zinc oxide whisker, aluminum nitrate whisker, aramid fiber, alumina fiber, silicon carbide fiber, ceramic fiber, asbestos fiber, gypsum fiber, and metal fiber. Examples of non-fibrous fillers include silicates such as wollastonite, zeolite, sericite, kaolin, mica, pyrophyllite, bentonite, asbestos, and alumina silicate; metal oxides such as alumina, magnesium oxide, zirconium oxide, titanium oxide, and iron oxide; metal carbonates such as calcium carbonate, magnesium carbonate, and dolomite; metal sulfates such as calcium sulfate and barium sulfate; metal hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide; glass beads, ceramic beads, boron nitride, and silicon carbide. These may be hollow. In addition, it is preferable to pretreat these fibrous and / or non-fibrous fillers with a coupling agent before use in order to obtain better mechanical properties. Examples of the coupling agent include isocyanate compounds, organic silane compounds, organic titanate compounds, organic borane compounds, and epoxy compounds.

[0055] Examples of copper compounds include copper chloride, copper bromide, copper iodide, copper acetate, copper acetylacetonate, copper carbonate, copper fluoroborate, copper citrate, copper hydroxide, copper nitrate, copper sulfate, and copper oxalate. The copper compound may contain two or more of these. Among these copper compounds, those that are industrially available are preferred, and copper halides are suitable. Examples of copper halides include copper iodide, copper bromide, copper bromide, and copper chloride. The copper compound is more preferably copper iodide.

[0056] Examples of potassium compounds include potassium iodide, potassium bromide, potassium chloride, potassium fluoride, potassium acetate, potassium hydroxide, potassium carbonate, and potassium nitrate. The potassium compound may contain two or more of these. Among these potassium compounds, potassium iodide is preferred. By containing a potassium compound, the surface appearance, weather resistance, and mold corrosion resistance of the molded product can be improved.

[0057] The potassium compound inhibits the liberation and precipitation of copper, and therefore, it is believed that the combined use of a copper compound and a potassium compound has the effect of promoting the reaction between the copper compound and the polyamide resin (A).

[0058] Examples of the thermoplastic resins include polyamide resins other than the component (A), polyester resins, polyphenylene sulfide resins, polyphenylene oxide resins, polycarbonate resins, polylactic acid resins, polyacetal resins, polysulfone resins, tetrafluoroethylene resins, polyetherimide resins, polyamideimide resins, polyimide resins, polyethersulfone resins, polyetherketone resins, polythioetherketone resins, polyetheretherketone resins, styrene-based resins such as polystyrene resins and ABS resins, and polyalkylene oxide resins. Two or more of such thermoplastic resins can be blended. When a polyamide resin other than the component (A) is blended, it is preferable that the amount is 5 parts by weight or less per 100 parts by weight of the polyamide resin (A).

[0059] Examples of the rubbery polymer other than component (B) include styrene-based rubbers other than component (B), olefin-based resins, acrylic rubbers, silicone-based rubbers, fluorine-based rubbers, nitrile-based rubbers, vinyl-based rubbers, urethane-based rubbers, polyamide elastomers, polyester elastomers, ionomers, etc. These may have reactive functional groups, and two or more of these may be blended together.

[0060] The structure of the rubbery polymer is not particularly limited, and may be, for example, a so-called core-shell type multilayer structure consisting of at least one layer made of rubber and one or more layers made of a different type of polymer. The number of layers constituting the multilayer structure may be two or more, and may be three or more or four or more, but it is preferable to have one or more rubber layers (core layers) inside. The type of rubber constituting the rubber layer of the multilayer structure is not particularly limited, and examples thereof include rubbers obtained by polymerizing acrylic components, silicone components, styrene components, nitrile components, conjugated diene components, urethane components, ethylene components, propylene components, isobutene components, etc. The type of different polymers constituting the layers other than the rubber layer of the multilayer structure is not particularly limited as long as they are polymers having thermoplasticity, but polymers having a higher glass transition temperature than the rubber layer are preferred. Examples of polymers having thermoplasticity include polymers containing unsaturated carboxylic acid alkyl ester units, unsaturated carboxylic acid units, unsaturated glycidyl group-containing units, unsaturated dicarboxylic acid anhydride units, aliphatic vinyl units, aromatic vinyl units, vinyl cyanide units, maleimide units, unsaturated dicarboxylic acid units, and other vinyl units.

[0061] Examples of the various additives include color inhibitors, antioxidants such as hindered phenols and hindered amines, release agents such as ethylene bisstearylamide and higher fatty acid esters, plasticizers, heat stabilizers, lubricants, ultraviolet protection agents, colorants, flame retardants, and foaming agents.

[0062] Next, the method for producing the thermoplastic elastomer composition of the present invention will be described. Examples of the method for producing the thermoplastic elastomer composition of the present invention include a method of kneading polyamide resin (A), copolymer (B) and other components as necessary all at once, and a method of blending and kneading a part of polyamide resin (A) and copolymer (B) and other components as necessary from a side feed during melt kneading. As the kneading device, for example, a known kneading device such as a Banbury mixer, a roll, or an extruder can be used. When blending other components such as various additives into the thermoplastic elastomer composition of the present invention, these can be blended at any stage. For example, when the thermoplastic elastomer composition of the present invention is produced using a twin-screw extruder, examples of the method include a method of blending other components simultaneously when blending polyamide resin (A) and copolymer (B), and a method of blending other components by a method such as side feed during melt kneading of polyamide resin (A) and copolymer (B).

[0063] The thermoplastic elastomer composition of the present invention can be molded by any method to obtain a molded product, and the molded shape can be any shape. Examples of the molding method include extrusion molding, injection molding, blow molding, calendar molding, compression molding, vacuum molding, foam molding, blow molding, and rotational molding. Examples of the molded shape include pellets, plates, fibers, strands, films or sheets, pipes, hollows, boxes, and the like.

[0064] The thermoplastic elastomer composition of the present invention can be foamed. Examples of the foaming method include a method of adding a foaming agent for foaming the thermoplastic elastomer when melt-kneading the thermoplastic elastomer composition, and then molding after melt-kneading; a method of dry-blending a foaming agent for foaming the thermoplastic elastomer composition with the thermoplastic elastomer composition of the present invention before molding, and then molding; a batch method of impregnating a thermoplastic elastomer composition molded in an autoclave with a supercritical gas to foam it; and a continuous method of impregnating a thermoplastic elastomer composition with a supercritical gas to foam it when melt-kneading it, and physical foaming. From the viewpoint of productivity and quality, physical foaming is preferred.

[0065] The supercritical gas used in physical foaming is not particularly limited as long as it can dissolve in the thermoplastic elastomer composition and is inactive, but carbon dioxide and nitrogen are preferred from the standpoint of safety and cost. The supercritical gas is preferably used in an amount of 0.01 to 20 parts by weight, more preferably 0.05 to 10 parts by weight, per 100 parts by weight of the thermoplastic elastomer composition.

[0066] The molded article of the present invention has excellent vibration damping properties, high-temperature rigidity, and blocking resistance, and can therefore be used in, for example, automobiles, electrical and electronic applications, etc. EXAMPLES

[0067] The effects of the present invention will be described more specifically below with reference to examples. Note that the present invention is not limited to the following examples. Evaluations in each example and comparative example were performed by the following methods.

[0068] (1) Melting point of polyamide resin (A) The melting point of the polyamide resin (A) used in each Example and Comparative Example was determined by DSC. First, a differential scanning calorimeter (PerkinElmer DSC-7) was used, and two-point calibration (indium, lead) and baseline correction were performed. 8 to 10 mg of the polyamide resin (A) was weighed out and heated at a heating rate of 20°C / min, and the melting endothermic peak temperature observed during the heating process was taken as the melting point.

[0069] (2) Amino end group amount of polyamide resin (A) The amount of amino terminal groups in the polyamide resin (A) used in each of the Examples and Comparative Examples was determined by dissolving the polyamide resin (A) in a phenol / ethanol mixed solvent (83.5:16.5 (volume ratio)) and titrating it with a 0.02 N hydrochloric acid solution.

[0070] (3) Glass transition temperature of copolymer (B) The glass transition temperature of the copolymer (B) used in each Example and Comparative Example was determined by viscoelasticity measurement. First, a strip of 40 mm x 8 mm x 1 mmt was cut out from a flat plate of 80 mm x 80 mm x 1 mmt made using the copolymer (B) kept in an absolute dry state, and measured using a viscoelasticity measuring device (Seiko Instruments, DMS6100) under conditions of a nitrogen atmosphere, a frequency of 10 Hz, and a heating rate of 2 ° C. / min to determine the storage modulus and loss modulus. The loss modulus was divided by the storage modulus to determine the loss tangent. The peak temperature of the determined loss tangent was taken as the glass transition temperature.

[0071] (4) High temperature stiffness: Melting point The melting point of the thermoplastic elastomer composition pellets obtained in each of the Examples and Comparative Examples was determined by DSC measurement. First, a differential scanning calorimeter (PerkinElmer DSC-7) was used, and two-point calibration (indium, lead) and baseline correction were performed. 8 to 10 mg of the thermoplastic elastomer composition was weighed and heated at a heating rate of 20°C / min, and the melting endothermic peak temperature observed during the heating process was taken as the melting point.

[0072] (5) Vibration damping: loss tangent (tan δ) Using the thermoplastic elastomer compositions obtained in each of the Examples and Comparative Examples, strips of 40 mm x 8 mm x 1 mm were cut out from the prepared 80 mm x 80 mm x 1 mm flat plates, and measured using a viscoelasticity measuring device (Seiko Instruments, DMS6100) under nitrogen atmosphere, at a heating rate of 2°C / min and a frequency of 100 Hz to determine the storage modulus and loss modulus. The loss tangent was calculated by dividing the loss modulus at a temperature of 23°C by the storage modulus.

[0073] (6) Productivity: Blocking The pellets obtained in each of the Examples and Comparative Examples were vacuum dried at 80° C. for 15 hours, and adhesion (blocking) between the pellets was confirmed during this process.

[0074] (7) Spinnability: High-speed take-up Thermoplastic elastomer composition pellets obtained in each Example and Comparative Example were vacuum dried for 15 hours at 80° C. The vacuum dried pellets were filled into a cylinder (cylinder diameter 9.55 mm, orifice length 10.0 mm, inner diameter 1.0 mm) manufactured by Toyo Seiki Seisakusho Co., Ltd., with the test temperature set at 280° C., compressed, and held for 30 minutes to melt, and then discharged under the condition of an extrusion speed of 3 mm / min. The discharged thermoplastic elastomer composition was judged as A if it could be taken up at a take-up speed of 200 m / min, as B if it could be taken up at a take-up speed of 150 m / min, and as C (poor spinnability) if it could not be taken up at a take-up speed of 150 m / min.

[0075] (8) Sheet formability Thermoplastic elastomer composition pellets obtained in each of the Examples and Comparative Examples were vacuum dried at 80° C. for 15 hours. The vacuum dried pellets were melted and kneaded at a discharge rate of 2 kg / hr using an extruder set at 250° C., and the resin was extruded in a certain direction from a die set at a clearance of 1 mm and formed into a sheet by fixing it on a roll set at 40° C. Those that could be molded into a sheet were judged as ◯ (good sheet moldability), and those that could not be molded into a sheet were judged as × (poor sheet moldability).

[0076] The raw materials and their abbreviations used in each of the Examples and Comparative Examples are shown below. PA6-1: Polyamide 6 resin (melting point 224°C, amino end group amount 4.8×10 -5 mol / g, relative viscosity 2.35 at 25°C in 98% concentrated sulfuric acid solution with a resin concentration of 0.01 g / ml) PA6-2: Polyamide 6 resin (melting point 224°C, amino end group amount 5.7×10 -5 mol / g, relative viscosity 2.70 at 25°C in 98% concentrated sulfuric acid solution with a resin concentration of 0.01 g / ml) PA6-3: Polyamide 6 resin (melting point 224°C, amino end group amount 4.5×10 -5 mol / g, relative viscosity at 25°C in 98% concentrated sulfuric acid solution with a resin concentration of 0.01 g / ml: 2.47) PA6-4: Polyamide 6 resin (melting point 224°C, amino end group amount 9.0×10 -5 mol / g, relative viscosity 2.30 at 25°C in 98% concentrated sulfuric acid solution with a resin concentration of 0.01 g / ml) PA12: Polyamide 12 resin (melting point 178°C, amino end group amount 4.8×10 -5 mol / g, relative viscosity at 25°C in 98% concentrated sulfuric acid solution with a resin concentration of 0.01 g / ml: 2.10) Copolymer-1: Maleic anhydride modified styrene-ethylene-butylene-styrene block copolymer 100 parts by weight of "SOE" (registered trademark) S1605 manufactured by Asahi Kasei Corporation was dry-blended with 1.4 parts by weight of maleic anhydride, 0.15 parts by weight of Perhexa 25B (manufactured by NOF Corporation, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane), and 0.1 parts by weight of Irgafos P168 (manufactured by BASF, tris(2,4-di-tert-butylphenyl)phosphite), and the mixture was fed to a twin-screw extruder (TEX30XSSST manufactured by JSW, L / D=45.5 (where L is the length from the raw material supply port to the discharge port, and D is the screw diameter)) with a cylinder temperature set to 230°C, melt-kneaded, and maleic anhydride was grafted to obtain copolymer-1. The copolymer-1 obtained was extracted and purified with acetone, and after drying, the amount of maleic anhydride added was determined by titration with sodium methylate, which showed that 1.3 wt% of maleic anhydride had been added. The glass transition temperature of the copolymer-1 obtained was measured to be 18°C. Copolymer-2: Maleic anhydride modified styrene-ethylene-butylene-styrene block copolymer 100 parts by weight of "SOE" (registered trademark) S1611 manufactured by Asahi Kasei Corporation was dry-blended with 1.4 parts by weight of maleic anhydride, 0.15 parts by weight of Perhexa 25B (manufactured by NOF Corporation, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane), and 0.1 parts by weight of Irgafos P168 (manufactured by BASF, tris(2,4-di-tert-butylphenyl)phosphite), and the mixture was fed to a twin-screw extruder (TEX30XSSST manufactured by JSW, L / D=45.5 (where L is the length from the raw material supply port to the discharge port, and D is the diameter of the screw)) with a cylinder temperature set to 230°C, melt-kneaded, and maleic anhydride was grafted to obtain copolymer-2. The copolymer-2 obtained was extracted and purified with acetone, and after drying, the amount of maleic anhydride added was determined by titration with sodium methylate, which showed that 1.3 wt% of maleic anhydride had been added. The glass transition temperature of the copolymer-2 obtained was measured to be 9°C. Copolymer-3: Maleic anhydride modified styrene-hydrogenated vinylisoprene-styrene block copolymer 100 parts by weight of "HYBRA" (registered trademark) 7125 manufactured by Kuraray Co., Ltd. were dry-blended with 1.4 parts by weight of maleic anhydride, 0.15 parts by weight of PERHEXA 25B (manufactured by NOF Corp., 2,5-dimethyl-2,5-di(t-butylperoxy)hexane), and 0.1 parts by weight of Irgafos P168 (manufactured by BASF, tris(2,4-di-tert-butylphenyl)phosphite), and the mixture was fed to a twin-screw extruder (TEX30XSSST manufactured by JSW Co., Ltd., L / D=45.5 (where L is the length from the raw material supply port to the discharge port, and D is the screw diameter)) with a cylinder temperature set to 230°C, melt-kneaded, and maleic anhydride was grafted to obtain copolymer-3. The copolymer-3 obtained was extracted and purified with acetone, and after drying, the amount of maleic anhydride added was determined by titration with sodium methylate, which showed that 1.3 wt% of maleic anhydride had been added. The glass transition temperature of the copolymer-3 obtained was measured to be -6°C. Copolymer-4: Maleic anhydride modified styrene-ethylene-butylene-styrene block copolymer 100 parts by weight of "Tuftec" (registered trademark) H1062 manufactured by Asahi Kasei Corporation was dry-blended with 1.4 parts by weight of maleic anhydride, 0.15 parts by weight of Perhexa 25B (manufactured by NOF Corporation, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane), and 0.1 parts by weight of Irgafos P168 (manufactured by BASF, tris(2,4-di-tert-butylphenyl)phosphite), and the mixture was fed to a twin-screw extruder (TEX30XSSST manufactured by JSW, L / D=45.5 (where L is the length from the raw material supply port to the discharge port, and D is the diameter of the screw)) with a cylinder temperature set to 230°C, melt-kneaded, and maleic anhydride was grafted to obtain copolymer-4. The copolymer-1 obtained was extracted and purified with acetone, and after drying, the amount of maleic anhydride added was determined by titration with sodium methylate, which showed that 1.3 wt% of maleic anhydride had been added. The glass transition temperature of the copolymer-4 obtained was measured to be -47°C. Copolymer-5: Maleic anhydride modified styrene-ethylene-butylene-styrene block copolymer 100 parts by weight of "SOE" (registered trademark) S1605 manufactured by Asahi Kasei Corporation was dry-blended with 0.8 parts by weight of maleic anhydride, 0.10 parts by weight of Perhexa 25B (manufactured by NOF Corporation, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane), and 0.1 parts by weight of Irgafos P168 (manufactured by BASF, tris(2,4-di-tert-butylphenyl)phosphite), and the mixture was fed to a twin-screw extruder (TEX30XSSST manufactured by JSW, L / D=45.5 (where L is the length from the raw material supply port to the discharge port, and D is the diameter of the screw)) with a cylinder temperature set to 230°C, melt-kneaded, and maleic anhydride was grafted to obtain copolymer-5. The copolymer-5 obtained was extracted and purified with acetone, and after drying, the amount of maleic anhydride added was determined by titration with sodium methylate, which showed that 0.7 wt% of maleic anhydride had been added. The glass transition temperature of the copolymer-5 obtained was measured to be 18°C. Copolymer-6: Maleic anhydride modified styrene-ethylene-butylene-styrene block copolymer 100 parts by weight of "SOE" (registered trademark) S1605 manufactured by Asahi Kasei Corporation was dry-blended with 2.2 parts by weight of maleic anhydride, 1.80 parts by weight of Perhexa 25B (manufactured by NOF Corporation, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane), and 0.1 parts by weight of Irgafos P168 (manufactured by BASF, tris(2,4-di-tert-butylphenyl)phosphite), and the mixture was fed to a twin-screw extruder (TEX30XSSST manufactured by JSW, L / D=45.5 (where L is the length from the raw material supply port to the discharge port, and D is the diameter of the screw)) with a cylinder temperature set to 230°C, melt-kneaded, and maleic anhydride was grafted to obtain copolymer-6. The copolymer-6 obtained was extracted and purified with acetone, and after drying, the amount of maleic anhydride added was determined by titration with sodium methylate, which showed that 2.0 wt% of maleic anhydride had been added. The glass transition temperature of the copolymer-6 obtained was measured to be 18°C. Unmodified copolymer: styrene-ethylene-butylene-styrene block copolymer (Tuftec (registered trademark) H1062, manufactured by Asahi Kasei Corporation, glass transition temperature -47°C).

[0077] [Examples 1 to 9, Comparative Examples 1 to 7] The raw materials listed in Table 1 were fed to a twin-screw extruder (TEX30XSSST manufactured by JSW Co., Ltd., L / D=45.5 (where L is the length from the raw material supply port to the discharge port, and D is the screw diameter)) with a cylinder temperature set to 250 ° C, a screw arrangement with two kneading zones, and a screw rotation speed of 250 rpm, melted and kneaded, and the gut discharged from the die was passed through a cooling bath filled with water adjusted to 10 ° C for 15 seconds to quench and fix the structure, and then pelletized with a strand cutter to obtain pellets. The obtained pellets were molded into a flat plate of 80 mm x 80 mm x 1 mmt using an injection molding machine (SE-75DUZ-C2 50 manufactured by Sumitomo Heavy Industries, Ltd.) under molding conditions of a mold temperature of 80 ° C, an injection speed of 40 mm / sec, and a cooling time of 60 seconds. The temperature of the injection molding machine was set at 240° C.-245° C.-250° C.-250° C. from the bottom of the hopper to the tip. The pellets or molded products obtained were evaluated by the above-mentioned methods, and the results are shown in Table 1.

[0078] [Table 1]

[0079] From the above results, it was found that the melting point measured by differential scanning calorimetry (DSC) was 200°C or higher and the amino terminal group amount was 4.7×10 -5 ~8.0×10 -5 The thermoplastic elastomer composition was obtained by blending 1.0 mol / g polyamide resin (A) and a copolymer (B) having a glass transition temperature of -20°C or more and 50°C or less, the copolymer (B) containing a polymer block mainly made of an aromatic vinyl compound having a reactive functional group and a polymer block mainly made of a conjugated diene compound and / or a hydrogenated product thereof, the composition ratio (weight ratio) of the polyamide resin (A) and the copolymer (B) being (A):(B)=50:50-80:20. The thermoplastic elastomer composition was found to be excellent in high temperature rigidity, vibration damping properties, blocking resistance and spinnability. [Industrial Applicability]

[0080] The thermoplastic elastomer composition of the present invention can be easily molded using a general-purpose melt molding technique, and has excellent vibration damping properties, spinnability, high-temperature rigidity and blocking resistance, and can be particularly suitably used in automotive applications, electrical and electronic applications, consumer applications, etc.

Claims

1. A melting point of 200° C. or higher as measured by differential scanning calorimetry (DSC) and an amino terminal group content of 4.7×10 -5 ~8.0 x 10 -5 mol / g of polyamide resin (A) and copolymer (B) having a glass transition temperature of -20°C or more and 50°C or less, the copolymer (B) comprising a polymer block mainly made of an aromatic vinyl compound having a reactive functional group and a polymer block mainly made of a conjugated diene compound and / or a hydrogenated product thereof, wherein the composition ratio (weight ratio) of polyamide resin (A) to copolymer (B) is (A):(B)=50:50 to 80:

20.

2. 2. The thermoplastic elastomer composition according to claim 1, wherein the polyamide resin (A) has a relative viscosity of 1.5 to 3.0 in a 98% concentrated sulfuric acid solution having a resin concentration of 0.01 g / ml at 25° C.

3. The thermoplastic elastomer composition according to claim 1, wherein the polymer block mainly composed of a conjugated diene compound and / or its hydrogenated product is a polymer block derived from at least one member selected from the group consisting of isoprene, butadiene, ethylene-butylene, and ethylene-propylene.

4. The thermoplastic elastomer composition according to claim 1, wherein the thermoplastic elastomer composition has a loss tangent of 0.05 or more at a frequency of 100 Hz and a temperature of 23°C.

5. A molded article comprising the thermoplastic elastomer composition according to any one of claims 1 to 4.

6. A fiber comprising the thermoplastic elastomer composition according to any one of claims 1 to 4.

7. A sheet comprising the thermoplastic elastomer composition according to any one of claims 1 to 4.

8. A foam-molded article comprising the thermoplastic elastomer composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Thermoplastic resin composition

    JP2006291117A